2020
DOI: 10.1172/jci.insight.141321
|View full text |Cite
|
Sign up to set email alerts
|

Single cell transcriptomics of mouse kidney transplants reveals a myeloid cell pathway for transplant rejection

Abstract: Myeloid cells are increasingly recognized as major players in transplant rejection. Here, we used a murine kidney transplantation model and single cell transcriptomics to dissect the contribution of myeloid cell subsets and their potential signaling pathways to kidney transplant rejection. Using a variety of bioinformatic techniques, including machine learning, we demonstrate that kidney allograft–infiltrating myeloid cells followed a trajectory of differentiation from monocytes to proinflammatory macrophages,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 81 publications
3
38
0
Order By: Relevance
“…So far, only limited information on the use of scRNA-seq in murine kidney transplantation has been published. Anil Dangi et al reported whole transcriptomics of mouse kidney transplants on day 15 in a single cell level and identified 13 immune cell clusters (13). In the present study, we developed further in-depth analysis of these immune cell types with comprehensive classification and description of cell subtypes including their specific marker genes, functional characteristics, transcriptional regulation, and the proportional dynamics from the renal allograft rejection peak on D7 to the regression phase on D15.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…So far, only limited information on the use of scRNA-seq in murine kidney transplantation has been published. Anil Dangi et al reported whole transcriptomics of mouse kidney transplants on day 15 in a single cell level and identified 13 immune cell clusters (13). In the present study, we developed further in-depth analysis of these immune cell types with comprehensive classification and description of cell subtypes including their specific marker genes, functional characteristics, transcriptional regulation, and the proportional dynamics from the renal allograft rejection peak on D7 to the regression phase on D15.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly 452 cells expressing markers of both T cells and macrophages/neutrophils were filtered as doublets. Next, 4,254 and 2,871 CD45 + leukocytes passing criteria of quality control were extracted from GSM4761000 and GSM4761003, respectively (Supplementary Figures 2, 3A-C) (13). Then, Seurat was used for integrating D7 and D15 data, and unsupervised clustering (14).…”
Section: Scrna-seq Identified Major Immune Cell Types In Mouse Kidney Allograftsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the R package edgeR ( 12 ) to normalize and analyze significantly differentially expressed lncRNAs (DElncRNAs), miRNAs (DEmiRNAs), and mRNAs (DEmRNAs) between the carboplatin-resistant OV group (n = 14) and the carboplatin-nonresistant OV group (n = 84). According to the previous study ( 13 ), we wanted to obtain more candidates. So, the cutoff values were |log2 fold change| ≥ 0.4 and p < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…By evaluating the typical C1qa , Cd74 , and Adgre1 expression, macrophages are defined as the predominant immune cells in diabetic glomeruli and mainly M1-like macrophages ( 90 ). The scRNA-seq analysis revealed that both extent and levels of Axl expression increased in F4/80 + macrophages from rejecting allografts compared to tolerized kidneys; and Axl promotes the differentiation of intra-graft myeloid cells towards pro-inflammatory phenotypes after transplantation ( 82 ). Moreover, the combination of scRNA-seq and lineage tracing technique attracts particular attention.…”
Section: Single-cell Rna-sequencing Revolutionmentioning
confidence: 99%